Subclinical myocyte injury, fibrosis and strain in relationship to coronary plaque in asymptomatic HIV-infected individuals. (10th September 2016) - Fitch, Kathleen V.; DeFilippi, Christopher; Christenson, Robert; Srinivasa, Suman; Lee, Hang; Lo, Janet; Lu, Michael T.; Wong, Kimberly; Petrow, Eva; Sanchez, Laura; Looby, Sara E.; Hoffmann, Udo; et al.
Abstract : Background: Cardiovascular disease (CVD) rates are increased in HIV. The degree to which myocyte injury, strain, and fibrosis occur prior to clinical disease and relate to coronary plaque in HIV is unknown. Objective: To investigate newer cardiac biomarkers of subclinical myocyte injury [high-sensitivity troponin T (hs-cTnT)], strain (amino terminal proB-type natriutretic peptide), fibrosis (soluble ST2, Galectin-3), and vascular inflammation (oxidized LDL, lipoprotein-associated phospholipase A2) in HIV-infected individuals and non-HIV controls and relate these to coronary plaque by cardiac computed tomography angiography. Design: Observational. Methods: Markers were investigated in 155 HIV-infected and 70 non-HIV-infected participants without known CVD and with low traditional CVD risk and related to cardiac computed tomography angiography data. Results: Age, sex, and race did not differ between the groups. Hs-cTnT [3.1 (3.0, 6.4) vs. 3.0 (3.0, 4.0) ng/l, P  = 0.03], Galectin-3 [13.5 (10.6, 18.1) vs. 11.6 (9.9, 14.5) ng/ml, P  = 0.002], and soluble ST2 [31.5 (24.5, 41.5) vs. 28.3 (20.2, 33.5) ng/ml, P  = 0.01] were significantly higher in HIV-infected participants vs. controls. Detectable hs-cTnT (seen in 50% of HIV participants) related to the overall presence of plaque [odds ratio (OR) 2.3, P  = 0.01] and particularly to coronary calcium (OR for Agatston calcium score > 0, 3.3, P  = 0.0008 and OR for calcified plaque 7.4, P  = 0.01) in HIV, but not in non-HIV. Conclusion: Subclinical myocyte injury is observed among young, asymptomatic HIV-infected individuals with low traditional cardiac risk factors. In the setting of HIV infection, the presence of detectable cardiac troponin is strongly associated with coronary plaque, particularly calcified plaque among an asymptomatic group. Future studies are needed to assess if early subclinical injury marked by hs-cTnT predicts plaque progression and cardiac events in HIV. Abstract : Supplemental Digital Content is available in the text